Leadership communication - Barrett, Deborah (McGraw-Hill Higher Education, 2010)
Leadership Communication was well received by students and instructors, and the second edition builds on that momentum. It continues to help current and potential managers become effective leaders by being better communicators. It brings together managerial communication and concepts of emotional intelligence to create a new model of communication skills and strategies for corporate leaders. It begins with chapters on the core communication skills of developing strategy, analyzing an audience, writing in all types of business genres, and designing and delivering effective PowerPoint presentations all from a leadership perspective. Then, it takes students through chapters on emotional intelligence, cultural literacy, meeting management, and team leadership, before concluding with chapters on internal and external organizational communication.